Assessment of students’ perception of research in an honors thesis preparation course (Research, Society and Development, 2023)
Identifying student’s perception of research activity can provide important practical implications to effectively recommend and facilitate research opportunities for students. Through two surveys applied at the beginning and end of an undergraduate honors orientation class we conducted a qualitative and quantitative study to assess the students’ knowledge and perception of research. The survey questions were repeated in two different semesters, and students were taught research related content. Even though 48% of the students did not have any research experience and a minority (12%) had more than a year of research experience, a large portion of the students could explain many research related words, such as plagiarism, citations, google scholar, and primary source, but a few words could not be recognized by the students, such as predatory journal, preprint, ORCID and publons. The most frequent answers provided by students when asked about their perception of researcher skills included the word motivation, followed by creativity and communication. Students’ confidence in their knowledge and research-related skills increased over the semester consistent with other studies that show the value of a structured introduction to research for building student confidence.